Step-by-step explanation:
please find the attached document
Answer:
3
Step-by-step explanation:
To turn the word problem into an equation, when we read:
"I am thinking of a number" we write "x"
"when I double my number" we write "2x"
"and then subtract the result from 5" we write "5 - 2x"
"I get negative one" we write "-1 = 5 - 2x"
Now we solve for the number, which is x.
<em>Equation: </em>-1 = 5 - 2x
-1 = 5 - 2x
subtract 5 from both sides
-6 = -2x
divide both sides by -2
3 = x
<h3>
There we go! The number is </h3><h2>
3</h2>
Need help myself not sure sorry
X^2 + 10x + 11 = 0
x^2 + 10x = -11
x^2 + 10x + 25 = -11 + 25
(x + 5)^2 = 14 <===
x + 5 = (+-) sqrt 14
x = -5 (+-) 3.74
x = -5 + 3.74 = -1.26 <== solution
x = -5 - 3.74 = - 8.74 <== solution